Peningkatan kesadaran masyarakat terhadap pencegahan stunting melalui edukasi gizi di Dusun Gunung Tumpuk, Desa Sidoluhur - Naf’an, Muhammad Ali; Antika, Wulan Dari Widi (Maliki Interdisciplinary Journal, 2024)
Stunting remains a significant nutritional challenge in Indonesia, characterized by children having shorter height than the standard for their age due to prolonged nutritional deficiencies. One effective intervention to address this issue is nutritional education. This community service program was carried out in Dusun Gunung Tumpuk, Desa Sidoluhur, aiming to raise public awareness, particularly among pregnant women and mothers of toddlers, regarding the importance of balanced nutrition in preventing stunting. The methods employed included interactive lectures, discussions, and hands-on demonstrations of preparing nutritious meals using locally available food sources. Additionally, parenting education was provided to enhance caregiving practices that support children’s optimal growth and development. The findings indicate an increased awareness in the community about the necessity of adequate nutrition from pregnancy until a child reaches two years of age. Through a community-based educational approach, this initiative is expected to contribute to reducing stunting rates and supporting the Sustainable Development Goals (SDGs) in improving the well-being of Indonesian children.